Sonification of plantar pressure in runners with and without pain after running practice - Vitor Tessutti; Anthony A. R. Diniz; Leonardo Signorini; Heliana Bezerra Soares; Milena C. Vidotto; Liu Chiao Yi (Termedia Publishing House, 2024)
Purpose Humans interact with the environment using sensory channels. Although vision is the main sensory channel, the auditory channel is excellent for learning when trained. Movement learning via auditory inputs requires sound analysis, such as sonification. Methods Data on peak plantar pressure from 43 recreational runners were collected using Flexinfit resistive insoles. Participants wore Run Falcon 1.0 (Adidas) running shoes and were categorised into four groups: without pain; spine or hip pain; thigh or knee pain; and leg, ankle, or foot pain. Participants responded to whether they presented pain and whether it was related to running (training or races). Sonification data were collected using the TwoTone software. We used the C note in the first octave to transform numerical data into sounds according to the pressure magnitude. The sound file was decomposed using the Audacity software into a spectrogram illustrating the main frequency components and their amplitudes. Results The spectrogram made it possible to identify qualitative differences between the runners with and without pain after running. The frequency spectrum showed that some frequencies had greater sound intensity in runners without pain. Conclusions Our results indicated differences between runners with and without pain after running using sonification. The frequency spectrum also indicated a difference in the sound intensity produced between the groups at specific frequencies.